Evaluating documentation of social history in paediatric medical notes at a regional paediatric centre - a quality improvement initiative - DJ Foley; JK Hannon; CS O'Gorman; AM Murphy (BMC, 2020)
Abstract Background A child's home and family environment plays a vital role in neuro-cognitive and emotional development. Assessment of a child's home environment and social circumstances is an crucial part of holistic Paediatric assessment. Aims Our aim is to achieve full compliance with comprehensive documentation of biopsychosocial history, for all children medically admitted to the children's inpatient unit in University Hospital Limerick. Methods We performed a retrospective chart review to audit documentation within our department. This was followed by teaching interventions and a survey on knowledge, attitudes and behaviour of paediatric non-consultant hospital doctors (NCHDs) towards the social history. We performed two subsequent re-audits to assess response to our interventions, and provided educational sessions to seek improvement in quality of care. Results Results showed a significant improvement in quality of documentation following interventions, demonstrated by a net increase of 53% in levels of documentation of some social history on first re-audit. Though this was not maintained at an optimum level throughout the course of the year with compliance reduced from 95% to 82.5% on second re-audit, there was nonetheless a sustained improvement from our baseline. Our qualitative survey suggested further initiatives and educational tools that may be helpful in supporting the ongoing optimisation of the quality of documentation of social history in our paediatric department. Conclusion We hope this quality improvement initiative will ultimately lead to sustained improvements in the quality of patient-centred care, and early identification and intervention for children at risk in our community.